SURVEY ON AWARENESS OF PATIENTS WERE SUFFERED WITH DIABETES MELLITUS, ABOUT ALTERNATIVE MEDICAL SYSTEMS IN UVA, NORTH CENTRAL PROVINCES AND MULLAITHIVU, MANNAR, KILLINOCHCHI DISTRICTS IN NORTHERN PROVINCE OF SRI LANKA - L.S.B, *Nuwansiri; S.R, Abeysooriya; M.G.T.C, Thilakarathne; G.K.M, Pathirana; L.D.C, Peiris; M.A.F, Mirfaha; T, Uthyagowry; G, Thusitha; M.M.F, Rispana (International Journal of Ayurveda and Pharma Research, 2016)
Diabetes Mellitus is becoming fastest considerable disease in the world. It is a metabolic disorder may result in deficiency or dysfunction of insulin production. The concept of Ayurveda that mentioned which are the loss of urinary disorders specially characterized by profuse urination with several abnormal qualities due to Dhosic imbalances. According to the Siddha concept first increase Azhal dhosha, then increase Vali dhosha, after that again increase Vali and Ayyam dhoshas increased in same time disturbance of seven Dhathus function and eliminate body energy through urine. The concept of Unani that mentioned Zinbatus shukkari (Diabetes Mellitus) develops due to weakness of the kidney including with strong exposures power and weakness of the retentive power due to causative factors. The prevention method is the most suitable pathway for control this considerable disease. Awareness of people should be increased to fulfill that purpose, and all the medical systems should be come to proper way of combination. Ayurveda, Siddha, Unani are the other alternative medical systems can be provide awareness of treatment except of allopathic system. To find out the awareness of people about other alternative medical systems can control Diabetes Mellitus and a find out proper way of continuation of diabetes clinics in these medical systems. In the methodology, prepared questionnaire to collect details. Details were found traveled to Sidda, Unani, Ayurveda district hospitals, Central dispensaries and free Ayurveda dispensaries in Uva, North central and Killinochhi, Mannar, Mullaithivu districts. There is low percentage of hospitals provide Diabetes clinics (Uva-20%, North central -11%, Killinochchi, Mannar, Mullaithivu districts -25%). Approximately 40 patients record for clinics. 50% of patients concern for only Ayurveda, Siddha, Unani treatments for Diabetes in these areas.